The new markets ... and other essays - Drucker, Peter F. (London : Heinemann, 1971)
The subject of this book is the environment in which executives and institutions work and perform. The present volume is more concern with economic, political, and social processes: the early diagnosis of fundamental social and economic change; the relationship between thought - economic, political or social - and actions; the things that work and don't work in certain traditions, whether those of America or those of Japan; or the conditions of effective leadership in the complex structures of industrial society and giant government.
Includes bibliographical references and index.
hza 31/07/2018
Loans
Keywords: Economic history; Business